The prince and the prodigal - Smith, Jill Eileen, 1958- (Revell, a division of Baker Publishing Group, 2022)
"Two brothers among twelve. One pampered. One petulant. After a stunning betrayal, Judah struggles to forget what he's done while Joseph attempts to move on from what's been done to him. Is there hope for reconciliation for one of Egypt's most powerful men and his wayward brother?"--